THE ETHICAL CONSIDERATIONS OF NURSES IN A PROFESSIONAL CONTEXT - Mona Ahmed Mathkur, Ibraheem Mohamed Alwazrah, Abdullah Mohammed Nasser Alqahtani, Aishah Shoei Mohammed Maghfoori, Haya Mohammed Nasser Alqahtaniy,; Abdulmajeed Saud Alsuwaydaa, Abdullah Mohammed Alsahman, Amira Barrak Aldhefri, Koloud Misnid Aldofiri, Hanan Sabah Alenazi, Rauf Fahad Hawbani, Afaf Ali Jbbari,; Tahani Ahmad Yahya Alguzi, Waleed Yahia Arishi, Amal Ali Ahmed Qubuli (Chelonian Research Foundation, 2022)
Ethical sensitivity is recognized as a fundamental element of ethical behavior. Lack of ethical awareness may lead to providing care that is not aligned with the ethical standards expected of nursing professionals. Therefore, it is crucial to evaluate ethical sensitivity in order to develop strategies that promote ethical behavior and to ensure that nurses understand the full scope of their professional ethical responsibilities. The purpose of this study is to evaluate and analyze the current state of knowledge on the ethical sensitivity of nurses, and to combine the results from several research. A thorough computerized search was conducted to find relevant material published in the Cumulative Index of Nursing and Allied Health material and PubMed. The data was extracted, reduced, and synthesized using a methodical methodology. Four primary conceptualizations of ethical sensitivity were identified in the literature. Although a concept analysis and a validated technique exist, ethical sensitivity is still a highly speculative topic with various, and often conflicting, interpretations. While ethical sensitivity has been thoroughly evaluated in the context of ethical challenges, there has been less focus on its application in everyday situations. Future study should prioritize the development of more effective methods to measure and evaluate the notion, specifically emphasizing the extent to which nurses are aware of the ethical aspects of their daily work. Keywords: Ethical sensitivity, review, nurses, nursing professionals, ethical behavior.